Characterization of Long‐Term Durability of Induction Welded Aluminum/Carbon Fiber Reinforced Polymer‐Joints1. Issue 9 (19th August 2013) - Didi, Mirja; Emrich, Stefan; Mitschang, Peter; Kopnarski, Michael
<x xml:space="preserve">Abstract</x> The long‐term durability of hybrid structures (metal – carbon fiber reinforced polymer) are investigated in this study using outdoor aging tests. For the metallic adherend different pre‐treatment methods were used before welding. The welded samples were exposed to the environment for 6, 9 and 12 months and afterwards tested by lap shear tests. The different pre‐treatment methods show great influence of the bonding quality with respect to the exposed time. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>